Analysis of the Technical Ability of the Indonesian Women's Volleyball Team Sea Games 2023 - B Bujang; Aridhotul Haqiyah; Mohamad Noor Mohamed (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
Understanding the technical skills required for success in volleyball is critical as the game continues to evolve, with an emphasis on the speed and precision of attacks. The purpose of this study is to determine the level of technical ability of the Indonesian women's volleyball team Sea Games 2023. This is a descriptive qualitative study with a sample of 14 athletes and uses percentages to summarise and interpret the data. The techniques analysed are divided into two parts, which are attacking techniques consisting of serves, attacks, blocks and defensive techniques consisting of serve reception and defence. The results showed that the attacking techniques of the Indonesian women's volleyball team had good attacking abilities, but the ability to serve and block was extremely weak, many serves and blocks failed and resulted in points for the opponent. For defensive techniques, the Indonesian women's volleyball team has excellent service reception ability, most of the service receptions can produce attacks both attacks that produce points and limited attacks. However, the defensive ability was very poor, most of the defences failed and resulted in points for the opponent. Finally, this study concludes that the poor performance of the Indonesian women's volleyball team is related to very weak serving, blocking and defence. So, the Indonesian women's volleyball team has to improve on serving, blocking, and defence techniques.